2013
DOI: 10.4317/medoral.18376
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ATP bioluminescence as a tool to assess antimicrobial effects of mouthrinses in an in vitro subgingival-biofilm model

Abstract: Objectives. The aim of this investigation was to evaluate whether the adenosine triphosphate (ATP) bioluminescence method is an appropriate tool to assess the efficacy of antiseptic mouthrinses in terms of quantitative reductions of total viable microbial counts in mixed biofilm populations in vitro. Study Design. Three mouthrinses, containing respectively, chlorhexidine and cetylpyridinium chloride (CHX/CPC), essential oils (EO) and amine fluoride/stannous fluoride (AFSF), as well as Phosphate Buffered Salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…The model presents several advantages over previously existing models (16)(17)(18)(19)(20)(21), in that we were able to consistently establish 35 species, compared with the previous maximum of 5 to 10 species (18,20,21). Further, the Calgary Biofilm Device afforded a high-throughput system to grow several repeats of biofilms with good consistency across pegs and plates, as evidenced by the high minimum similarity coefficient values.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The model presents several advantages over previously existing models (16)(17)(18)(19)(20)(21), in that we were able to consistently establish 35 species, compared with the previous maximum of 5 to 10 species (18,20,21). Further, the Calgary Biofilm Device afforded a high-throughput system to grow several repeats of biofilms with good consistency across pegs and plates, as evidenced by the high minimum similarity coefficient values.…”
Section: Discussionmentioning
confidence: 71%
“…The first step in such an endeavor is to demonstrate efficacy against subgingival microorganisms in vitro, ideally in models involving organized biofilms that respond like those in vivo. Currently used in vitro oral multispecies biofilm models all suffer from one or more limitations, generally comprising only up to 5 or 10 species (16)(17)(18)(19)(20)(21). In addition, existing models lack reproducibility and have low throughput (17,19).…”
mentioning
confidence: 99%
“…In contrast, ATP is a precise and valid metric previously applied to similar oral biofilm testing. ATP of dispersed oral biofilm cells after treatment was successfully used to quantitate relative efficacy of mouthrinses and mouthrinse ingredients (Pan et al, 2010;Sánchez et al, 2013). Sánchez et al (2013) also found that viable cell counts and ATP levels were significantly (p b 0.001) correlated.…”
Section: Discussionmentioning
confidence: 96%
“…Sánchez et al [40] evaluated the antimicrobial effect of three commercial mouthrinses (0.12% CHX plus 0.05% CPC, EO, and fluoride/stannous fluoride -AFSF) on mixed periodontopathogenic biofilm (S. oralis, V. parvula, A. naeslundii, F. nucleatum, A. actinomycetemcomitans and P. gingivalis) in vitro using ATP bioluminescence and CFU methods. 72h-biofilm was exposed to mouthrinses or control for 1 min.…”
Section: Commercial Agents and Biofilm/mentioning
confidence: 99%